RIZWAN KHAN'S EXISTENCE IN KARAN JOHAR'S MY NAME IS KHAN MOVIE (2010): AN EXISTENTIALIST APPROACH - TRIWARJIANTO, ALFIAN (2011)
This study is aimed to show Rizwan Khan existence in My Name Is Khan movie by using existentialist perspective. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the Existentialist Approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the My Name Is Khan movie directed by Karan Johar released in 2010. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, setting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form unity. Second, based on the Existentialist analysis, awareness of the meaning of human existence is very important.